Fecal microbial transplantation as a novel therapeutic for autism spectrum disorders: a review of the current literature - Gudka, Rebecca; Nyinoh, Iveren Winifred (Frontiers in Microbiomes, 2023)
Background Autism spectrum disorders (ASDs) are complex neurobiological conditions with poor long-term outcomes and limited treatment options. The microbiota–gut–brain axis indicates a pathway by which the gut microbiota links to ASDs. Fecal microbial transplantation (FMT), whereby the gut microbiota is replaced with that of a healthy individual, shows promise for the treatment of neurobiological conditions. This review examines the current evidence for the use of FMT as a therapeutic for ASD. Discussion ASDs and their associated gastrointestinal symptoms are improved with FMT, potentially due to the engraftment of features of a healthy gut. Longer treatment regimens that include daily maintenance doses appear to be the most effective long-term therapeutic option, with benefits persisting 2 years post-intervention. Evidence is mixed regarding the use of preparatory treatments. Considering the sex bias in ASD research, small sample sizes and the lack of placebo control arms, randomized controlled trials would be of benefit to the evidence base regarding the use of FMT as a therapeutic option for ASD. Conclusion FMT is a promising new therapeutic for ASD, but the evidence base is in its infancy.